STUDY OF THE MINERALOGICAL STRUCTURE OF MAIN DOWNSTREAM DRAIN SEDIMENTS AND ITS IMPACT IN BEHAVIOR OF NICKEL AND COBALT - Al Maamouri, Abdul Baqi D.S.; Shref, Ashrf M.; Isa, Husian Abdali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was conducted to determine the nature of the mineral structure and properties of carbonate minerals of the sediments of the Main downstream and their effect on the chemical behavior of nickel and cobalt in five areas of Baghdad Governorate: Abu Ghraib, Al-Radwaniyah, Al-Yusufiyah, Al-Mahmoudiyah, and Al-Latifiyah. The results showed a difference, to the clay minerals of the water stream sediments. The presence of clay minerals such as mica, smectite, true chlorite, and swollen chlorite was observed in varying proportions, and the latter appeared more at the end of the study area. While a decrease in the percentage of kaolinite minerals was observed, a difference was observed in the quantity and properties of carbonate minerals, and the active part of them increased at the end of the study area. The chemical behavior of nickel and cobalt also varied in association with clay and carbonate minerals. The association of nickel with carbonate minerals was greater than that of clay minerals, with a percentage of 53.7, 40.8, 38.9, 40.0, 53.3%, while the association of cobalt with clay minerals was greater than that of carbonate minerals, with a percentage of 49.4, 45.9, 55.4, 45.17, 44.1%, after extracting the association images for each element using the successive extraction technique in all five study areas, respectively.